Physical and mechanical properties of C class fly ash based lightweight geopolymer mortar produced with expanded vermiculite aggregate - Kaya, Mehmet; Köksal, Fuat (Revista de la Construcción. Journal of Construction, 2022)
This study presents the physical and the mechanical properties of C class fly ash (FA) based lightweight geopolymer mortars produced with expanded vermiculite (EV) aggregate. The FA was activated with NaOH containing 12%, 14% and 16% sodium by weight. The volumetric ratios of EV/FA in the samples were chosen as 2,4 and 6 in the study. The liquid/solid ratio 0.23, 0.26 and 0.29. Lightweight geopolymer mortar (LGM) samples were produced by mixing FA, EV, NaOH and water in a mixer. The samples placed in molds were exposed to activation temperature of 100°C for 24 hours in the oven. The samples taken out of the oven were demoulded and kept in air curing for 28 days at 20°C±2°C room temperature. After curing, unit weight, apparent porosity, water absorption ratio, ultrasonic pulse velocity (UPV), flexural strength and compressive strength tests were performed on the samples. In addition, the thermal conductivity coefficients of the samples were determined. As a result of the experiment, a compressive strength varying between 0.59 MPa and 3.81 MPa was obtained in lightweight geopolymers samples with a unit weight between 906 kg/m3 and 1477 kg/m3. Expanded vermiculite showed a good performance on thermal conductivity of LGMs and a decrease in thermal conductivity up to the 0.094 W/mK was observed.